COVID-19 and the Kidneys: An Update - Benedetti, Claudia; Waldman, Meryl; Zaza, Gianluigi; Riella, Leonardo V.; Cravedi, Paolo (Frontiers in Medicine, 2020)
Novel coronavirus disease 2019 (COVID-19) has become a worldwide emergency health problem. The disease occurs mostly in individuals between 30-79 years of age and 81% of cases are mild. However, it may result in progressive respiratory failure owing to alveolar damage and can be fatal in 3.6% of the cases. Direct viral injury, uncontrolled inflammation, and activation of coagulation and complement cascades are thought to participate in disease pathogenesis. Patients with COVID-19 often display kidney injury, including acute kidney injury, mild proteinuria, hematuria or slight elevation in creatinine, possibly as consequence of renal tropism of the virus and multiorgan failure. The impact of COVID-19 on patients that already have renal impairment, including those with chronic kidney disease, kidney transplant recipients, and individuals on hemodialysis (HD) has not been clearly established yet, but data are reports are accumulating and will be reviewed herein. Currently, there is no specific treatment for COVID-19. Research has revealed several agents that may have potential efficacy against COVID-19, mostly acting as anti-viral and anti-inflammatory drugs. Many of these molecules have demonstrated preliminary efficacy against COVID-19 and are currently being tested in clinical trials.